2015
DOI: 10.1021/acs.iecr.5b01624
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Level Understanding of Solvation Structures and Vibrational Spectra of an Ethylammonium Nitrate Ionic Liquid around Single-Walled Carbon Nanotubes

Abstract: Molecular dynamics simulations have been performed to explore the solvation structures and vibrational spectra of an ethylammonium nitrate (EAN) ionic liquid (IL) around various single-walled carbon nanotubes (SWNTs). Our simulation results demonstrate that both cations and anions show a cylindrical double-shell solvation structure around the SWNTs regardless of the nanotube diameter. In the first solvation shell, the CH 3 groups of cations are found to be closer to the SWNT surface than the NH 3 + groups beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…In addition, the confined cations have a shoulder before the conventional asymmetric N–H stretching vibrational peak at 3344 cm –1 . Above vibrational spectra are different from those of other interfaces such as EAN–air, EAN–carbon nanotube, and water–Au nanoparticle. , Some previous works , have confirmed that the characteristic asymmetric stretching vibration peak of N–H at 3344 cm –1 is due to HBs between EAN ion pairs. For the EAN IL molecules confined inside the TiO 2 slits, the EA + cations can form two types of HBs: one with the TiO 2 wall and the other with the NO 3 – anions.…”
Section: Results and Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In addition, the confined cations have a shoulder before the conventional asymmetric N–H stretching vibrational peak at 3344 cm –1 . Above vibrational spectra are different from those of other interfaces such as EAN–air, EAN–carbon nanotube, and water–Au nanoparticle. , Some previous works , have confirmed that the characteristic asymmetric stretching vibration peak of N–H at 3344 cm –1 is due to HBs between EAN ion pairs. For the EAN IL molecules confined inside the TiO 2 slits, the EA + cations can form two types of HBs: one with the TiO 2 wall and the other with the NO 3 – anions.…”
Section: Results and Discussionmentioning
confidence: 85%
“…R c ON /θ c ONH corresponds to the distance/angular criterion for HB formation, respectively. According to previous works, the values for R c ON and θ c ONH were set to 3.7 Å and 30°, respectively. We calculated the average HB number between the EA + cations and NO 3 – anions and between the EA + cations and the TiO 2 walls in the first layers of the four systems, as shown in the Table .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We calculated the vibrational spectra from molecular dynamics simulations by Fourier transform to velocity autocorrelation function (VACFs). The normalized velocity autocorrelation function is dened as [72][73][74][75]…”
Section: Dynamical Properties Of the Mixturesmentioning
confidence: 99%